GoDonnie: A robot programming language for teaching people who are visually impaired - Oliveira, Juliana Damasio; Campos, Márcia de Borba; Amory, Alexandre M.; Bordini, Rafael H. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2019)
Recent work indicates that many programming environments and languages are difficult for people who are visually impaired to use, which may contribute to excluding them from a professional career in computing. This work aims to create and evaluate the use of a programming language called GoDonnie for students who are visually impaired. We developed a programming language that students use to simulate a robot’s behavior. We also introduce two usability studies that were conducted with end-users. The initial results indicate that our programming language is easy to learn by beginners and experienced programmers alike. In addition, users report high levels of enjoyment when programming in GoDonnie.